DINAMIKA MOTIVASI PADA ANAK BERBAKAT DALAM MENARI (STUDY KASUS ANAK MADRASAH IBTIDAIYAH KELAS 5 DI SIDOARJO) - arofah, nur; setyawan, wahyu aris (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Abstract Many of our children are still bury their talents, it is because they feel less confident to their abilities. So that, their talents are not channeled. We as parents and teachers must motivate our children. Because gifted children are different from smart children. Talent means to have potential, while being smart can be obtained by learning something diligently. Although persevering, but not potential, a person will not be able to be as optimal as gifted child. For this reason, the aim of this research is that we as parents and teachers provide full motivation for our children to feature their talents. The subjects in this research is a child who has talent in dancing. The results of this study indicates that the environment is very influential in the dynamics of talent children motivation. In the research process of subject environment both at school and at home is very supportive, but the subject is easily discouraged when there is a talk that offends the subject. Keywords: Motivation, Gifted Children, Dancing